Recent progress in fungus-derived bioactive agents for targeting of signaling machinery in cancer cells - Lin X; Farooqi AA; Ismail M (Dove Medical Press, 2015)
Xiukun Lin,1 Ammad Ahmad Farooqi,2 Muhammad Ismail2 1Department of Pharmacology, Capital Medical University, Beijing, People’s Republic of China; 2Institute of Biomedical and Genetic Engineering, Islamabad, Pakistan Abstract: It is becoming increasingly understood that tumor cells may have different mutations and dependencies on diverse intracellular signaling cascades for survival or metastatic potential. Overexpression of oncogenes, inactivation of tumor suppressor genes, genetic/epigenetic mutations, genomic instability, and loss of apoptotic cell death are some of the mechanisms that have been widely investigated in molecular oncology. We partition this multicomponent review into the most recent evidence on the anticancer activity of fungal substances obtained from in vitro and xenografted models, and these fungal substances modulate expression of oncogenic and tumor suppressor miRNAs.  There are some outstanding questions regarding fungus-derived chemical-induced modulation of intracellular signaling networks in different cancer cell lines and preclinical models. Certain hints have emerged, emphasizing mechanisms via which apoptosis can be restored in TRAIL-resistant cancer cells. Reconceptualization of the knowledge obtained from these emerging areas of research will enable us to potentially identify natural agents with notable anticancer activity and minimal off-target effects. Integration of experimentally verified evidence obtained from cancer cell line gene expression with large-scale functional screening results and pharmacological sensitivity data will be helpful in identification of therapeutics with substantial efficacy. New tools and technologies will further deepen our understanding of the signaling networks that underlie the development of cancer, metastasis, and resistance to different therapeutics at both a personal and systems-wide level. Keywords: fungal products, cell signaling, cancer, apoptosis, miRNA, xenograft